2016
DOI: 10.14260/jemds/2016/1536
|View full text |Cite
|
Sign up to set email alerts
|

Choristoma of Liver - A Case Report

Abstract: BACKGROUNDChoristoma or Ectopic Liver is a rare condition in which the hepatic tissue is located at a site away from its usual anatomical location. It is incidentally identified during laparotomy or laparoscopy for other disorders. Resection of the ectopic liver en bloc with the gall bladder is the standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Based on 72 reports reviewed in this study, the average size of the ectopic liver tissue was found to be 17.8 mm. In the literature, the reported size of ectopic livers (without hepatocellular carcinoma) ranges from a few millimeters to several centimeters[ 24 , 44 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on 72 reports reviewed in this study, the average size of the ectopic liver tissue was found to be 17.8 mm. In the literature, the reported size of ectopic livers (without hepatocellular carcinoma) ranges from a few millimeters to several centimeters[ 24 , 44 , 58 ].…”
Section: Discussionmentioning
confidence: 99%